TUTOR–STUDENT PSYCHOLOGICAL INTERACTION MODEL AND ITS IMPACT ON ACADEMIC PERFORMANCE (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2026)
This study examines the impact of psychological interaction between tutors and students on academic performance within higher education. The relevance of the topic is обусловed by the increasing need for individualised learning approaches and psychological support in modern educational environments. The primary aim of the research is to develop a model of tutor–student psychological interaction and to empirically assess its influence on students’ academic outcomes. A quantitative research design was employed, involving a survey of more than 100 university students. The collected data were analysed using descriptive statistics, correlation, and regression analyses. Key psychological components of tutor–student interaction, including communication quality, level of trust, and emotional support, were evaluated as independent variables, while academic performance indicators such as grade point average (GPA), motivation, and attendance were considered dependent variables. The findings reveal a significant positive relationship between effective psychological interaction and academic performance (r = 0.61–0.75). In particular, higher levels of emotional support and trust were associated with improved academic achievement and increased student motivation. The proposed interaction model demonstrates the critical role of psychological factors in enhancing learning outcomes. In conclusion, the results highlight the importance of integrating psychological dimensions into tutoring systems and suggest that the developed model can contribute to improving academic effectiveness in higher education institutions.